Ceria-based model catalysts: fundamental studies on the importance of the metal–ceria interface in CO oxidation, the water–gas shift, CO2 hydrogenation, and methane and alcohol reforming. (17th February 2017) - Rodriguez, José A.; Grinter, David C.; Liu, Zongyuan; Palomino, Robert M.; Senanayake, Sanjaya D.
Abstract : Model metal/ceria and ceria/metal catalysts have shown to be excellent systems for studying fundamental phenomena linked to the operation of technical catalysts. Abstract : Model metal/ceria and ceria/metal catalysts have been shown to be excellent systems for studying fundamental phenomena linked to the operation of technical catalysts. In the last fifteen years, many combinations of well-defined systems involving different kinds of metals and ceria have been prepared and characterized using the modern techniques of surface science. So far most of the catalytic studies have been centered on a few reactions: CO oxidation, the hydrogenation of CO2, and the production of hydrogen through the water–gas shift reaction and the reforming of methane or alcohols. Using model catalysts it has been possible to examine in detail correlations between the structural, electronic and catalytic properties of ceria–metal interfaces. In situ techniques (X-ray photoelectron spectroscopy, X-ray absorption spectroscopy, infrared spectroscopy, scanning tunneling microscopy) have been combined to study the morphological changes under reaction conditions and investigate the evolution of active phases involved in the cleavage of C–O, C–H and C–C bonds. Several studies with model ceria catalysts have shown the importance of strong metal–support interactions. In general, a substantial body of knowledge has been acquired and concepts have been developed for a more rational approach to the design of novel technical catalysts containing ceria.